Examining the Efficiency of Zakat Management: Indonesian Zakat Institutions Experiences - Solahuddin Al-Ayubi; Ascarya .; Bayu Taufiq Possumah (International Journal of Zakat, 2018)
This study evaluates the efficiency of Indonesian Zakat Institutions (IZI), including technical, pure technical and scale efficiencies using a production approach. This study also examines the sources of inefficiency. By employing the Data Envelopment Analysis (DEA) technique, this study proposes a solution to improving the efficiency of IZI. The input variables of this study are the number of amil, the number of volunteers, the number of offices, socialization costs, personnel costs, and operational costs. The output variables of this study include the amount of zakat collected, the distribution of consumptive zakat, the distribution of productive zakat, the number of muzakki and the number of mustahiq. The results indicate that between 2010-2013 IZI Mass technical efficiency were higher than IZI Non-Mass on average. In 2014, IZI Non-Mass exceeded IZI Mass technical efficiency. IZI Mass pure technical efficiency had an upward trend during 2011-2013, but then declined during 2014-2016. However, IZI Non-Mass pure technical efficiency experienced an upward trend during 2011-2012, then slightly decreased in 2013. Although the efficiency increased in 2014-2015, there was a subsequent decrease in 2016. After a period of fluctuation during 2011-2013, the scale efficiency of IZI Mass decreased in 2014 and stabilized in 2015-2016. Similarly, IZI Non-Mass fluctuated during 2011-2012, then stabilizing until 2016. The increasing problems of IZI Mass and IZI Non-Mass are the socialization costs, the number of volunteers, the amount of zakat collected, and the distribution of consumptive zakat, which cumulatively reduces the intermediation function of zakat institutions. IZI must resolve these issues to ameliorate the efficiency of zakat institutions. Keywords: Indonesian Zakat Institutions, Efficiency, Technical Efficiency JEL Classification Code: L31, D61